The Clinical Significance Of Freezing While Turning in Parkinson’s Disease - Mancini, Martina (Neuroscience, 2016)
Freezing of gait (FoG) in people with Parkinson’s disease (PD) is an environmentally sensitive, intermittent problem that occurs most often during turning. FoG is difficult for clinicians to evaluate and treat because it can be difficult to elicit during a clinical visit. Here, we aimedto develop a clinically valid objective measure of freezing severity during a 2-minute 360 degrees turning-in-place. Twenty-eight subjects with PD (16 freezers, FoG+, and 12 nonfreezers, FoG−) in the “off” state and 14 healthy control subjects were tested. Subjects wore 3 inertial sensors (one on each shin and one on the waist) while 1) turning in place for 2 minutes (alternating 360 degrees to the right with 360 degrees to the left) and 2) performing an Instrumented 7m Timed Up and Go test (ITUG). Performance was videotaped, and clinical severity of FoG was independently rated by two movement disorders specialists (co-authors). Turning in place consistently resulted in FoG (13 out of 16 subjects with PD) while FoG was clinically observed in only 2 subjects with PD during the ITUG test. The Freezing Ratio during the turning test was significantly correlated with the clinical ratings (ρ=0.7, p=0.003) and with score on the new freezing of gait questionnaire (ρ=0.5, p=0.03). After correcting for symptom severity (UPDRS-III), out of the 4 objective measures of the turning test (total number of turns, average turn peak speed and average turn smoothness), only the Freezing Ratio was significantly different across groups (p=0.04). Freezing can be well quantified with body-worn inertial sensors during a 2-minute turning-in-place protocol.